Attributes of a good nurse: The opinions of nursing students - Aydin Er, Rahime (Nursing ethics, 2017)
Background:The opinions of students regarding the attributes of a good nurse can make a major contribution to the planning and the conducting of professional education. There are few studies which aim at identifying the qualifications of a good nurse from the perspectives of nursing students.Objectives:To determine the opinions of first- and fourth-year nursing students concerning the ‘attributes of a good nurse’, and whether and how their views change depending on their year of study.Research design:Descriptive research.Participants and research context:This study was conducted in the nursing department of a vocational school of health in the 2010/2011 academic year. The study participants consisted of first-year and intern students. A survey form was used to identify characteristics of participants, and students were asked the following open-ended question about their opinions related to the attributes of a good nurse.Ethical considerations:The permission was taken from the school administration. Informed consent was obtained, and anonymity was ensured for participating students.Findings:A total of 120 students participated in this study. Most frequently expressed attributes were ‘professional competence’ in first-year and ‘responsibility’ in fourth-year students. While first-year students placed a greater emphasis on the attributes of ‘geniality’, ‘patience’, ‘calmness’, ‘love of nursing’, ‘loyalty to nursing’ and ‘not attaching importance to material values’, fourth-year students emphasized the attributes of ‘empathy’, ‘honesty’, ‘responsibility’ and ‘scientific curiosity’ significantly more.Discussion and conclusion:Fourth-year students placed a greater emphasis on the attributes which the students are expected to acquire through a nursing program and clinical experience. However, they mentioned the attributes related to a good nurse–patient relationship and communication significantly less. Appropriate ethical training methods and good role models can help students acquire attributes that are important for the nursing profession and combine them with the attributes they already have.